Identification Of Revenue In Banking In The City Of Medan - Aulia (International Journal of Management, Economic and Accounting, 2023)
This research aims to explore and identify the various sources and mechanisms contributing to revenue generation in the banking sector within the City of Medan. The study delves into the intricate details of revenue streams, assessing the diverse sources, instruments, and strategies employed by banks to generate income. Utilizing a mixed-methods approach, the research incorporates both quantitative data analysis and qualitative insights from key stakeholders within the banking industry. The quantitative aspect involves the analysis of financial statements, income reports, and performance indicators, providing a comprehensive overview of revenue trends. Key focal points of the research include the identification of interest income, fee-based income, and other ancillary sources contributing to the overall revenue of banks in Medan. The qualitative component involves interviews and discussions with banking executives and regulators to gather nuanced insights into the strategies employed for revenue diversification and sustainability. Preliminary findings indicate a diverse landscape of revenue sources, including traditional banking activities, innovative financial products, and digital services. The research contributes to the understanding of the dynamics of revenue identification in the banking sector, providing valuable insights for financial institutions, policymakers, and industry analysts.